2004
DOI: 10.1128/aac.48.11.4315-4321.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Characterization of Combined Pharmacodynamic Effects of Antimicrobial Agents

Abstract: There is considerable need for new modeling approaches in the study of combined antimicrobial effects. Current methods based on the Loewe additivity and Bliss independence models are associated with implicit assumptions about the interacting system. To circumvent these limitations, we propose an alternative approach to the quantification of pharmacodynamic drug interaction (PDI). Pilot time-kill studies were performed with 10 8 CFU of Pseudomonas aeruginosa/ml at baseline with meropenem or tobramycin alone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
(13 reference statements)
0
25
0
Order By: Relevance
“…2F. This combination has previously been shown to be synergistic when the two drugs are used concurrently (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2F. This combination has previously been shown to be synergistic when the two drugs are used concurrently (30).…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that meropenem and tobramycin exhibited synergistic killing when they were used in combination (30). Therefore, we examined the feasibility of adding an aminoglycoside to lower the meropenem pharmacodynamic threshold necessary to suppress resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to quantify arbitrary agent interactions are unsatisfactory as they are associated with multiple implicit assumptions of the interacting system; they have been reviewed in detail previously (5,25). Briefly, the fractional inhibitory concentration index (the most widely used method for the in vitro interaction of antimicrobial agents) is based on Loewe additivity, in which linear concentration-effect relationships are implicitly mandated for all agents in a combination.…”
Section: Discussionmentioning
confidence: 99%
“…Specific concentrations for each agent used (including a placebo control) were as determined in the previous section. The total bacterial burden at 24 h (in triplicate) was determined by quantitative culture as described above, and the data were mathematically modeled using a three-dimensional response surface as described previously (25). Briefly, effect summation was used as the definition of additivity (null interaction) (5), as follows:…”
Section: ) These Assessments Were Consistent With Observations Inmentioning
confidence: 99%
“…The concentration ranges examined were constrained to those clinically achievable in human serum (up to 40 mg/liter for both imipenem [5,12] and MK-7655 [unpublished data on file]); specific concentrations used were based on the best-fit parameter estimates and optimal sampling for the most precise characterization of bacterial killing. The total bacterial burden at 24 h (in triplicate) was mathematically modeled using a three-dimensional response surface as described in detail elsewhere (Mathematica 5.2; Wolfram Research, Inc., Champaign, IL) (18). Volumes under the plane (VUP) of the observed (VUP observed ) and expected (VUP expected ) surfaces were computed by interpolation and double integration, respectively.…”
Section: Methodsmentioning
confidence: 99%